Duodenal gunshot wounds: Primary surgical management - Rodríguez, Gustavo; Ruso, Luis; Praderi, Raúl (Cirugía del Uruguay, 1997)
Duodenal injuries due to fire-arms in civilians have increased in recent years. Authors present a retrospective study of 12 cases from Hospitals Maciel and Clnicas in a period of 7 years.